Effects of soaking time on the physico-chemical properties and sensory attributes of soya bean milk - Paragas, Carla Kay T.
Effects of five different soaking time treatments (6, 8, 10, 12, and 14 hours) on the physico-chemical properties and sensory attributes of soymilk were investigated.